SYMBOLISM AND METAPHOR IN DEPICTING HUMAN-AI RELATIONSHIPS IN KLARA AND THE SUN - Toirova Nargiza Isakovna; Abdurakhmonova Makhfiratkhon (TADQIQOTLAR, 2025)
Kazuo Ishiguro’s Klara and the Sun explores the intersection of artificial intelligence (AI) and human emotions, using powerful symbols and metaphors to delve into themes of hope, fragility, and social alienation. The novel’s central character, Klara, an AI, embodies innocence and emotional growth as she navigates human relationships and struggles to understand the complexities of human existence. Key symbols, such as the Sun, the store window, and the barn, illustrate the limitations and possibilities of AI while also highlighting the fragility of human life. By analyzing these symbols and metaphors, this paper examines how Ishiguro uses language and narrative style to convey deep insights into human nature and the boundaries between technology and emotion.